2016
DOI: 10.1016/j.jpedsurg.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in the very young: a comparative study of tumor markers, pathology and survival in early onset and adult onset patients

Abstract: Introduction Colorectal cancer (CRC) diagnosed before age 30 is a fatal disease whose biology remains poorly understood. To understand its pathogenesis, we compared molecular and clinical data in surgically treated early-age onset and adult onset patients. Materials and methods Clinical data and tumor tissue were collected retrospectively for 94 patients with early-age onset CRC (≤age 30) and compared to 275 adult CRC patients (≥age 50). Tumor morphology, microsatellite instability (MSI) and stability (MSS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 47 publications
5
81
1
1
Order By: Relevance
“…Although it is well established that dMMR can be accurately measured by directly enumerating known MSI loci using targeted deep sequencing (MSI-NGS) [31] or by TMB [32], our results warrant some caution, and further validation is needed to elucidate this aspect. However, our findings are in accordance with previous studies that showed that MSI-H occurs more frequently in younger patients, although frequencies vary widely [33,34], and that the pattern of mutations leading to MSI-H in younger patients is different from older patients [35,36]. In fact, currently, we are examining whether mutations in specific MMR genes have a different impact on immune-related biomarker expression (e.g., PD-L1 overexpression and TMB level).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although it is well established that dMMR can be accurately measured by directly enumerating known MSI loci using targeted deep sequencing (MSI-NGS) [31] or by TMB [32], our results warrant some caution, and further validation is needed to elucidate this aspect. However, our findings are in accordance with previous studies that showed that MSI-H occurs more frequently in younger patients, although frequencies vary widely [33,34], and that the pattern of mutations leading to MSI-H in younger patients is different from older patients [35,36]. In fact, currently, we are examining whether mutations in specific MMR genes have a different impact on immune-related biomarker expression (e.g., PD-L1 overexpression and TMB level).…”
Section: Discussionsupporting
confidence: 92%
“…Colorectal cancer (CRC) is the third most common cancer and the fourth leading cause of cancer-related death worldwide [1]. In the last 2 decades, adults aged 50 years have experienced increase by 90% and 124%, respectively, in patients aged 20-34 years and by 27.7% and 46.0%, respectively, in patients aged [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] years [3]. The cause remains unknown, although lack of screening, obesity, physical inactivity, and Western diets may play a crucial role in early-onset CRC.…”
Section: Introductionmentioning
confidence: 99%
“…These younger patients often present with more advanced disease and adverse pathological features compared to their older counterparts [7]. This may have a negative impact on their survival outcome [8].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence regarding young-onset CRC (yCRC) patient prognosis is conflicting. Some retrospective studies suggest that younger patients have a poorer prognosis than those with later-onset disease [8]. However, other studies suggest their prognosis is better or equivalent to those aged over 55 years [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation